Kebijakan Penta Helix Dalam Pengembangan Parawisata Musik di Kota Ambon - Manuputy, Leonard; Nataniel, Elake; J. Rolobessy, Mike (Jurnal Ilmiah Global Education, 2024)
Ambon City is known as the World Music City. As a music city, Ambon has a tourism appeal related to music. This research aims to understand the implementation of the Pentahelix policy by the Ambon City Government for the development of Ambon City as a World Music City, and to formulate and recommend strategies for collaboration among the Pentahelix actors in the implementation of the policy for the development of Ambon City as a World Music City. This research utilizes qualitative descriptive methods. The results of this study indicate that the Pentahelix policy model needs further optimization because the integrity among stakeholders is still low. Furthermore, there are several formulated recommendations and strategies that can be applied, including establishing a collaborative forum for Ambon music tourism, promoting communication among stakeholders, strengthening the AMO as a data hub and coordination center, making AMO an independent institution, stimulating communication and business initiatives, conducting research related to music tourism, developing an appropriate tourism calendar, educating and raising public awareness, conducting promotional campaigns through media, periodic monitoring and evaluation, as well as human resource development.